2024
DOI: 10.1039/d3fo03324d
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid fermentation of goji berries (Lycium barbarum) prevents acute alcohol liver injury and modulates gut microbiota and metabolites in mice

Wenhui Duan,
Lingxi Zhou,
Yilin Ren
et al.

Abstract: Juice fermented with lactic acid bacteria (LAB) has received attention due to its health benefits, such as antioxidant, and anti-inflammatory. Previous research on LAB-fermented goji juice mainly focused on exploring...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Indeed, the most predominant metabolite in our study is lactic acid: a result of the fermentation of rice by the LAB group bacteria. Lactic acid is also known to be anti-hypertensive, in addition to being bifidogenic [ 38 , 53 , 54 ]. Fermentation of polysaccharides has shown to produce Betaine, L-carnitine, and amino imidazole all of which upregulate the tyrosine and tryptophan biosynthesis pathways [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the most predominant metabolite in our study is lactic acid: a result of the fermentation of rice by the LAB group bacteria. Lactic acid is also known to be anti-hypertensive, in addition to being bifidogenic [ 38 , 53 , 54 ]. Fermentation of polysaccharides has shown to produce Betaine, L-carnitine, and amino imidazole all of which upregulate the tyrosine and tryptophan biosynthesis pathways [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unconventional fermented feed has significant effects on the antioxidant capacity of animals as it is rich in antioxidant substances, such as vitamins, polyphenolic compounds, and organic acids, that can effectively remove free radicals in the body, regulate redox balance, enhance antioxidant enzyme activity, and improve the antioxidant capacity of animals [ 164 ]. These antioxidants not only protect cells and tissues from oxidative damage, but also improve animal immunity, reduce the risk of disease, and promote the healthy growth and performance of animals [ 165 ]. The beneficial microbial metabolites and active substances in unconventional fermented feed have the effects of promoting the activity of antioxidant enzymes, directly or indirectly affecting the activity of antioxidant enzymes, and slowing down the occurrence of oxidative stress [ 166 , 167 ].…”
Section: Unconventional Fermented Feed Improves Oxidative Stress By R...mentioning
confidence: 99%
“…Plants 2024, 13, x FOR PEER REVIEW 14 of 24 of various metabolic diseases, including GI tract inflammation [153][154][155], nonalcoholic fatty liver disease [156], alcoholic liver disease [157], and diabetes [149,158,159]. Many studies have shown that LBPs could alleviate cognitive impairment and neuroinflammation caused by high-fat diets [148,160,161].…”
Section: Influence Of the Active Ingredients In Goji Berries On Gut M...mentioning
confidence: 99%
“…Through their complex influence on GI microbial interactions and interactions between microorganisms and their hosts, as well as the exchange and transformation of metabolites, the active ingredients in goji berries actively participate in immune regulation and energy metabolism and modulate neural messaging [ 152 ]. Therefore, they assist in the treatment of various metabolic diseases, including GI tract inflammation [ 153 , 154 , 155 ], nonalcoholic fatty liver disease [ 156 ], alcoholic liver disease [ 157 ], and diabetes [ 149 , 158 , 159 ]. Many studies have shown that LBPs could alleviate cognitive impairment and neuroinflammation caused by high-fat diets [ 148 , 160 , 161 ].…”
Section: Influence Of the Active Ingredients In Goji Berries On Gut M...mentioning
confidence: 99%